Experiencias de Consumo de Spa y Recuperacion: Compresiones De Los Factores Protectores Internos y Externos en Cuatro Adultos Con Vidas Ejemplarizantes (2016)
This research investigates by internal, external and elements related to the notion of the future that led to remain in recovery of four adults with consumer experience in order to understand how from this, protective factors achieved that today is constituted as cases or exemplary lives. For this, a qualitative descriptive methodology was designed. The technique for collecting information was an open interview. Internal and external protective factors protective factors were established as categories of analysis. It was identified in each of the participating skills and abilities that function as protective factors to mystify the likelihood of injury in an adverse situation. These people are characterized by resilient because they had the ability to overcome adversity and build from it a life project that currently meets.